Hydrothermal carbonization of corn straw in biogas slurry. (15th June 2022) - Jiang, Huier; Deng, Fang; Luo, Yiping; Xie, Zhijie; Chen, Yichao; Zhou, Pan; Liu, Xiaofeng; Li, Dong
Abstract: Hydrothermal carbonization of corn straw with biogas slurry (HTCBS) was studied, with the goal of recovering nutrients from biogas slurry (BS), producing slow-release fertilizer, and sequestration of CO2 . Specifically, the impacts of hydrothermal carbonization temperature (160–280 °C) and solid-to-liquid ratio (S/L) (1:5–1:25) on the characteristics of hydrochar and aqueous phase (AP) were investigated. Under the optimized hydrothermal carbonization condition at 250 °C and 1:10 S/L, total nitrogen, ammonia nitrogen and total phosphorus in AP decreased 30%, 64% and 91%, respectively, where total potassium increased 36% comparing with BS. Compared to traditional two-step hydrothermal carbonization followed by biogas slurry nutrient adsorption, HTCBS process was better suited for nutrient recovery (especially nitrogen and phosphorus) from BS. The proposed mechanism of nitrogen adsorption was the formation of C–N bond, and phosphorus was collected via the generation of metal phosphate precipitates, where potassium was released into AP from corn straw due to the high solubility in water. Additionally, a significant amount of humic substances (45 g/L) was obtained in AP of HTCBS. This study indicated the viability of HTCBS to recover nitrogen and phosphorus from BS, and potentially provide a potassium humate enriched water-soluble fertilizer. Graphical abstract: Image 1 Highlights: Biogas slurry was used as aqueous phase for hydrothermal carbonization of straw. N in biogas slurry is adsorbed onto hydrochar by forming a C–N bond. P in biogas slurry is retained on hydrochar by forming phosphate precipitation. K was released from corn straw to aqueous phase. Humic substances were produced in aqueous phase.